Desempenho, emissão de metano e qualidade da carne animais Nelore e cruzados Angus x Nelore terminados em dieta de alto teor de lipídios - Barbara Martins Rodrigues (2022)
The aim of this study was to evaluate performance, methane production, carcass characteristics and beef quality of Nellore and Nellore x Angus animals, finished in the feedlot with a high-lipid diet. The Ethics Committee approved all experimental procedures for Animal Use at the Federal University of Minas Gerais (UFMG, protocol number 71/2019). At the beginning of the project, the animals were divided into two groups according to their breed composition as follows: Nellore ((initial body weight (IBW) = 444,7 ± 47 kg, n = 25)) and Angus x Nellore crossbred (IBW = 509.8 ± 45.5 kg, n = 25). The animals came from the same breeding season, and before the feedlot, they stayed on a pasture of Megathyrsus maximus cv. Mombaça, with protein and energy supplement intake by 0.2% of B.W. The diet was composed for sorghum silage (20%), ground corn (57.6%), ground soybean seed as the lipid source (20.4%), and a mineral/vitamin premix (2%) (DM basis). Titanium dioxide (TiO2) was used as an external marker to estimate dry matter intake (DMI), while 10 g was administered to 12 animals of each group, once daily, for 10 d. Enteric methane emissions were measured using the sulfur hexafluoride (SF6) tracer gas technique in the same animals used for intake measurements. The animals were equipped with gas collection halters attached to pre-evacuated polyvinyl chloride (PVC) sampling canisters with a capillary tube (0.127 mm diameter), made to permit 50% filling in 24 h, for five consecutive days. The feedlot period was 126 days, and the animals were adapted to the experimental diets for the first 21 days. The diet was formulated using the Maximum Profit Ration® software for an average daily gain (ADG) of 1.6 kg/day. Initially, 50% of sorghum silage and 50% of concentrate diet were supplied, and the amount of concentrate was increased until the ratio of roughage: concentrate was 20:80 (DM basis). The soybean used in the concentrate was grounded and passed through a 5 mm mesh to increase the lipid ruminal availability. A day before slaughter, animals were weighed after a 16-hour fasting period to obtain the FBW and sent to the commercial slaughterhouse, where they were kept fasting for 24 hours with only ad libitum water access. The slaughter was conducted according to humanitarian procedures required by Brazilian legislation. Meat samples were taken between the 11st and 13rd ribs for analysis of total loss, drip loss, cooking loss, lipid oxidation of intramuscular and subcutaneous fat, shear force, color characteristics, centesimal composition, metabolomic composition, and fatty acid profile from intramuscular and subcutaneous fat. The crossbred animals had higher dry matter intake (DMI), feed efficiency, initial body weight (IBW), final body weight (FBW), average daily gain (ADG), average daily gain of carcass (ADGc), hot carcass weight (HCW), and percentage of rib (P < 0.01). The dressing percentage was similar for both groups (P > 0.05). Nellore animals produced more enteric methane expressed as g/kg ADG (P < 0.01), however, these animals had higher concentrations of polyunsaturated fatty acids (PUFA) and conjugated linoleic acid (CLA) in both longissimus thoracis (LT) muscle, and subcutaneous fat (P < 0,01). No difference was observed for total loss, drip loss, and cooking loss between genetic groups (P > 0.05). A gradual increase in lipid oxidation was observed as a function of time for both TBARS in the longissimus thoracis muscle and subcutaneous fat, especially at 42 days of aging time (P < 0.01). Shear force was influenced by breed and aging time (P < 0.01), in which Nellore animals presented higher values. There was a significant interaction between aging time and L*, a*, b* c*, and h* parameters (P < 0.01). The crossbred animals had a higher (P < 0.01) concentration of collagen, and Nellore had higher values of moisture in their LT muscle (P < 0.01). The genetic groups influenced the performance, carcass characteristics, and beef quality of the animals. The supply of soybean as a lipid source modified the fatty acid (FA) profile of LT muscle and subcutaneous fat.